DIMENTIONS OF HUMANISM: HISTORICAL-PHILOSOPHICAL ANALYSIS - Фоменко, А. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
On the basis of historical-philosophical analysis of humanistic invariants the article presents showing peculiarities of discourse of the époque of Renaissance, New Times and Postmodernism.